2018
DOI: 10.1016/j.mjafi.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

A study of clinical, radiological and etiological profile of cerebral venous sinus thrombosis at a tertiary care center

Abstract: Background: A prospective, observational study was done at a tertiary care hospital in Western Maharashtra to describe the etiologies, clinical features, diagnosis and prognosis of cerebral venous sinus thrombosis in an Indian population. Methods: 54 patients with clinical and MRI features suggestive of cerebral venous sinus thrombosis (CVST), were studied with detailed clinical evaluation and pro-thrombotic work up. All were followed up monthly for 6 months, to assess the response to therapy and clinical outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
2
3
1
Order By: Relevance
“…[7] Transverse sinus is the most commonly affected sinus in 77% of cases in a study. [16] In our study, the most effected sinus was transverse sinus in both groups similar to the other studies. However sagittal sinus involvement was higher in NIH group than IH group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[7] Transverse sinus is the most commonly affected sinus in 77% of cases in a study. [16] In our study, the most effected sinus was transverse sinus in both groups similar to the other studies. However sagittal sinus involvement was higher in NIH group than IH group.…”
Section: Discussionsupporting
confidence: 91%
“…The remarkable use of MRI and especially the increase in the use of MRV has made this diagnosis easier. [11] In previous studies, it is shown that MRI combine with MRV are current diagnostic modality of choice and are the best imaging technique for diagnosis of CVST in patients with unclear findings on CT. [16,17] DSA is the more effective for early diagnosis of dural sinüs lesions but the American Heart and Stroke Association recommend MRI and MRV as a preferred tests for the diagnosis of dural sinus lesions. [18] In our study, 92.3% patients underwent detailed radiological work-ups, including MRI and MRV to put the diagnosis easily.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort also, thrombophilia was the commonest etiology and constituted one-fourth of the cases (25.3%) followed by puerperal CVT (15.6%). Similar to Anadure et al ,[ 10 ] we found elevated factor VIII to be an important genetic thrombophilia causing CVT. In fact, both our male patients with CVT recurrence had highly elevated factor VIII levels {218% and 357% (normal factor VIII:60%–150%)}.…”
Section: Discussionsupporting
confidence: 90%
“…[ 3 8 ] Indeed, two recent studies from western India indicate that inherited thrombophilias may be replacing puerperal CVT as the dominant etiology in our country too. [ 9 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…(13) While Anadure et al reported the incidence of generalized, focal and focal with secondary generalized seizure in patients with CVT 65% , 25% and 10 % respectively. (14) In the present study, 55% patients had acute symptomatic seizure and 45% late seizure, which is quite higher than the reported by Mahale et al studied seizures in CVT and found that 46% of patients with CVT had acute seizures. (15) In this study male cases represent 6.9 % And female represent 93.1% of patients and this disagree with , Sha et al found that female patients represented 55 % of patients.…”
Section: Table (1) Comparison Between Status Epilepticus Group and Wi...contrasting
confidence: 67%